Loving Kindness and Capability in the Mathematics Classroom - Markle, Josh (Journal of the Canadian Association for Curriculum Studies, 2019)
I imagine mathematics to be a place of loving kindness and capability. Loving kindness is a way of being together, one that affords and sustains capability; and making the (math) classroom a place of loving kindness consists in taking an active interest in one other. Nussbaum (2011) characterizes capability as an answer to the following question: “What is each person able to do and to be?” (p. 18). Drawing on Nussbaum’s (2011) capabilities approach as a broad, normative framework for characterizing individual well-being in the context of teaching and learning, I inquire into my experience teaching a mathematics class in which we cooperatively built 14-foot Prospector canoes. I explore the potential for a hermeneutic pedagogy as a means to both interpret and cultivate capability, and to identify three specific, significant capabilities that emerged in our work together—autonomy, affiliation and hermeneutic imagination—as valuable in and of themselves, yet also essential to cultivating and securing additional capabilities, and to furnishing a space for loving kindness in the mathematics classroom.